Blueprint for Implementation of Intelligent System at Government Agencies - Ade Supriatna (UIN Sultan Syarif Kasim Riau, 2011)
The development of Information technology increasingly sophisticated. Intelligent System is the future of computer systems, especially for government agencies in decision-making. Preparation leading to the intelligent system must be done starting today. Starting from the vision, mision, goals and readiness of resources arranged in a blueprint. Various methodologies can be used to create a blueprint. The research will use Enterprise Architecture Planning (EAP). EAP in Enterprise Architecture is the planning process of defining architectures for the use of information in support of the business and the plan for implementing those architecture. EAP had a viewpoint that the business mission is the primary driver. That is followed by the data required to satisfy the mission, followed by the applications that are built using that data, and finally by the technology to implement the applications. Keywords : information technology, intelligent system, EAP, blueprint